Cervical Spine Clearance Guideline for Severe Head Injury Patients and Cervical Collar Related Complications - Pattanapongsa, Likana; Chotirosniramit , Narain; Chittawatanarat, Kaweesak (Biomedical Sciences and Clinical Medicine, 2022)
Objective Severe head injury patients commonly experience several negative effects from wearing a cervical collar for an extended period of time. This study was conducted to evaluate the results after cervical spine clearance guideline implementation. at a tertiary level-I University-hospital-based trauma center in the Northern region of Thailand. Methods This is retrospective pre- and post-guideline implementa-tion observational study included severe head injury patients who were admitted between January 2008 and December 2013. The pre- implementation phase (Pre) was January 2008 through October 2010 (34 months) and the post-implementation period (Post) was between November 2010 and December 2013 (38 months). The primary outcome was the incidence of cervical collar-associated decubital ulcer. P values less than 0.05 were considered statistical significance. Results A total of 899 patients with severe head injury were observed over 72 months (437 in Pre and 461 in Post). There were no significant differences in patient baseline characteristics with the exception of median age. The incidence of collar-related complications significantly decreased following introduction of the cervical spine clearance guideline [Pre 26 (5.95%) vs. Post, 8 (1.74%); p = 0.001] , the incidence of other decubital ulcers [90 (20.59%) vs. 64 (13.88%), p = 0.008], median cervical collar time in hour (interquartile range, IQR) [8 (22%) vs. 2 (13%), p < 0.001], and median time to diagnosis in hours [8 (23) vs. 1 (6), p < 0.001]. However, there were no differences in the implementation phases of intubation time or length of hospital and ICU stay. Conclusions Implementation of a cervical spine clearance guideline could decrease the incidence of collar-related decubital ulcer and shorten the cervical collar time as well as diagnostic time.